PENINGKATAN DAYA SAING PRODUK PERTANIAN APPOLI MELALUI PERBAIKAN KEMASAN DAN PEMANFAATAN DIGITAL MARKETING - Arief Iman Santoso (INOTEKS : Jurnal Inovasi Ilmu Pengetahuan, Teknologi, dan Seni, 2022)
Appoli (Boyolali Organic Rice Farmers Alliance) is an organization that functions to provide a forum for farmers in joint marketing and improving the quality of agricultural products. In developing Appoli's product marketing, there are several problems including the low competitiveness of products, especially packaging that is not yet marketable and their limited marketing reach. From the packaging side, the problem faced is the limitations of the packaging equipment, do not have the product and brand labels that characterize and characterize the products from Apoli. Website-based or digital-based information and marketing systems are needed to reach a wider market, not only regional markets but are expected to be able to reach markets outside the region or nationally. To overcome these problems, several activities were carried out, namely: 1) introduction of vacuum packaging equipment and the addition of plastic packaging 2) introduction of attractive and safe product packaging design 3) label and brand improvement 4) development of Appoli's product marketing website. It is expected that from a number of planned activities to be introduced, Appoli is able to increase product competitiveness and expand its marketing reach through digital marketing so that it can ultimately increase the income of the farming community.